Pengaruh Pendapatan Asli Daerah dan Flypaper Effect Terhadap Perilaku Oportunistik Penyusun Anggaran - Anita DeGrave; Raja Vanaldo Boang Manalu; Rein J Wekan (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
This study aims to test and analyze the effect of local revenue and flypaper effect on the opportunistic behavior of budget makers. The data used in this research is panel data from eleven districts/cities in Maluku province from 2014 to 2020. The analysis method used is panel data regression analysis. The results showed that: (1) Local Own Revenue has a positive and significant effect on the Opportunistic Behavior of Regency/City Budget Formers in Maluku. This means that the higher the District/City Original Revenue, the higher the Opportunistic Behavior of Budget Compilers; (2) The Flypaper Effect has a positive and significant effect on the Opportunistic Behavior of Regency/City Budget Formers in Maluku. This means that the higher the occurrence of flypaper effect in regencies/cities in Maluku, the higher the opportunistic behavior of budget makers; and (3) Simultaneously the Regional Original Income and the Flypaper Effect influence the Opportunistic Behavior of Regency/City Budget Formers in Maluku.